Human Resource Selection and Marketing: The Role of Human Resource Management in the Enterprise - Ignatius Septo Pramesworo; Sigit Sugiardi; Ida Harahap; Rezky Nurbakti; Dini Rosari (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This research aimed to explore the strategic role of HRM in selecting and marketing HR as a key asset for the company's success. The research focuses on how HRM can find and recruit talent that fits the organization's needs amid tough business competition. HR selection based on technical competence, behavior, and alignment with corporate values is seen as a crucial first step in building a strong resource foundation. Also, talent marketing strategies are important in a competitive job market. They include employer branding, career development, and employee engagement initiatives. They help attract and retain top talent. This study uses a qualitative approach to understand the processes and strategies that companies implement in HR selection and marketing. We collected data through in-depth interviews with HR managers. They were from five multinational companies in tech, manufacturing, and services. Also, watching the recruitment and training gave insights into the companies' internal dynamics and best practices. Document analysis such as recruitment policies, annual reports, and HR marketing strategies were also used to enrich the research data. The results show that a competency-based HR selection strategy. It improves recruitment and ensures new hires have the right skills to support the company's goals. On the other hand, integrated HR marketing has benefits. It boosts the company's image as an ideal workplace (employer branding). It also provides career development. This approach has increased the company's appeal to talent and strengthened employee loyalty. This approach significantly enhances a company's competitiveness in the global labor market.